Allelic Variation in Zmfatb Gene Defines Variability for Fatty Acids Composition Among Diverse Maize Genotypes - Katral, Ashvinkumar; Muthusamy, Vignesh; Zunjare, Rajkumar U.; Chhabra, Rashmi; Maman, Shalma; Yadava, Devendra K.; Hossain, Firoz (Frontiers in Nutrition, 2022)
Edible oil with lower saturated fatty acids is desired for perceived quality and health benefits to humans and livestock. fatb gene encoding acyl-ACP thioesterase is a key player in the conversion of palmitic acid to oleic acid, thereby modifying the ratio of saturated to unsaturated fatty acids in maize kernels. The present investigation characterised the full-length sequence of the Zmfatb gene (4.63 kb) in two mutants (Zmfatb) and eight wild-types (ZmfatB) inbreds to study allelic variation, gene-based diversity, phylogenetic-relationship, protein-modelling, and molecular-docking to identify novel candidates for modification of fatty acid profile. Sequence alignment revealed wide genomic variability for Zmfatb among the inbreds; identified five novel SNPs and two InDels that clearly differentiated the wild-type and mutant genotypes. Gene-based diversity using 11-InDel markers categorised 48-diverse maize-inbreds into two-clusters. The majority of mutant and wild-type inbreds were grouped in separate clusters and led to the generation of 41 haplotypes. Genetic relationship of maize fatb gene with orthologues among 40 accessions of 12 oilseed-crops using both nucleotide and protein sequence clustered maize, soybean, sunflower, opium-poppy, Citrulus lanata, quinoa, and prunus species into one cluster; and brassica, camelina, and arabidopsis into the different cluster. The clustering pattern revealed that the plant oil with higher unsaturated fatty acids, particularly oleic, linoleic, and linolenic acids grouped together in one cluster and higher proportions of other fractions like arachidic, eicosenoic, and erucic acids grouped in another cluster. Physico-chemical properties highlighted more similarity between maize and 29 orthologue proteins, but orthologues were found to have better thermostability. Homology models have been developed for maize mutant and wild-type inbreds using Umbellularia californica (PDB ID: 5x04) as a template. Predicted protein models possessed optimum confidence-score and RMSD values and validated stability via., Ramachandran plots. Molecular docking indicated most of the interactions of protein-ligand were having similar binding-affinity due to the broader specificity of fatty acyl-ACP thioesterases and the presence of conserved-domains across crops. This is the first report on the comprehensive molecular characterisation of the fatb gene in maize and various orthologues. The information generated here provided new insights into the genetic diversity of fatb gene which can be utilised for the enhanced nutritive value of oil in the breeding programme.